2023
DOI: 10.17645/mac.v11i1.6029
|View full text |Cite
|
Sign up to set email alerts
|

Mobile News Consumption and Its Relation to Young Adults’ Knowledge About and Participation in Referendums

Abstract: The news media are among the most important sources of information about political events, such as referendums. For young adults, the smartphone has become the main device for accessing news. However, we know little about the factors influencing mobile news consumption and how this consumption is related to political knowledge and political participation. This study investigates the antecedents of young individuals’ smartphone news consumption and how it is correlated with their knowledge about and participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The terms 'use' and 'consumption' are likely to be employed interchangeably. Most studies define consumption as the level of exposure to news (Yang & Patwardhan, 2004), while others describe it as news-use habits (Van Dijk, 2006) (Matthews, 2022;Su et al, 2022;Vogler et al, 2023). The literature showed that individuals' engagement with social media news differs from other types of news consumption because it can take various forms, with some being more active than others (Dvir-Gvirsman, 2022; Gajardo & Costera Meijer, 2022).…”
Section: Affective Vs Cognitive News Engagementmentioning
confidence: 99%
“…The terms 'use' and 'consumption' are likely to be employed interchangeably. Most studies define consumption as the level of exposure to news (Yang & Patwardhan, 2004), while others describe it as news-use habits (Van Dijk, 2006) (Matthews, 2022;Su et al, 2022;Vogler et al, 2023). The literature showed that individuals' engagement with social media news differs from other types of news consumption because it can take various forms, with some being more active than others (Dvir-Gvirsman, 2022; Gajardo & Costera Meijer, 2022).…”
Section: Affective Vs Cognitive News Engagementmentioning
confidence: 99%
“…In a tracking study combined with a survey, Vogler et al (2023) analyzed news consumption patterns of young adults in Switzerland in the run-up to a referendum, showing that the use of media content from traditional news media (on smartphones) and the use of social media have distinct effects on the duration and diversity of news consumption.…”
Section: Current Perspectives On Referendum Campaignsmentioning
confidence: 99%